Three Dimensional multi-UAV path planning using Modified Grey Wolf Optimizer - Dewangan, R. K; Bohat, V. K (International Journal of Computer Sciences and Engineering, 2025)
Robot path planning is a task to determine the most feasible path between origin and destination while avoiding collisions in the underlying environment. This task has always been characterized as a high dimensional optimization problem and is considered NP-Hard. Numerous algorithms have been proposed that provide solutions to the problem of path planning in a deterministic and non-deterministic way. However, the problem is open to new algorithms that have the potential to obtain better quality solutions with less time complexity. This paper presents a new approach to solve the problem of three- dimensional path planning of a flying vehicle while maintaining a safe distance from obstacles on the road. A new approach based on the modified grey wolf optimization algorithm is applied to the problem. The modified algorithm is compared to the standard GWO algorithm and have shown good results